Isolation of Acid Tolerant Peanut ( Arachis hypogaea L.) Rhizobia from Soils of Central Argentina - Taurian, Tania (1999)
Soil acidity may significantly reduce the symbiotic nitrogen fixation limiting Rhizobium survival and persistence in soils and reducing nodulation (Graham et al 1994). Recently it was determined that soils of Central Argentina (Córdoba) showed low content of organic matter and relatively low pH in all the analyzed horizons (Hammp et al 1997). Peanut is a very important crop in Argentina, since this country is the third in the world in peanut exportation. A detailed examination of composition of rhizobia peanut-nodulating native population in soils of Central Argentina has not been carried out yet. In this work, we present results on the isolation and characterization of native peanut-nodulating rhizobia from soils of Cordoba in Central Argentina.